Pelatihan Pembuatan Filter Air Sederhana Berbahan Alam untuk Meningkatkan Pemahaman Mahasiswa Fisika tentang Air Bersih - Dewi, Ratna Sari; Ridho, Dimas; Butar Butar, Hotma Br.; Simanullang, Vanessa Putri Rizky; Turnip, Kristian; Syadilla, Rina; Simbolon, Sarnika; Kembaren, Theresya Yolanda; Sinaga, Ririn Denita (Jurnal Abdimas Kesehatan (JAK), 2026)
Water is a vital necessity for human life, thus the quality of clean water must be maintained. However, observations in the Percut Sei Tuan River, Medan Tembung, revealed poor water quality characterized by turbidity, odor, and color changes caused by domestic and industrial pollution. To address this problem, a training program on constructing simple water filters using local materials such as sponge, activated carbon, coconut fiber, and gravel was conducted for Physics students of the Faculty of Mathematics and Natural Sciences, Universitas Negeri Medan. The activities included a pretest, field observation, hands-on filter construction, and a posttest. Results showed that the students’ average pretest score of 25.94 increased to 49.25 in the posttest, with a normalized gain of 0.32 categorized as moderate. The improvement covered knowledge, technical skills, and environmental awareness. The training effectively enhanced students’ conceptual understanding while providing practical experience in designing simple and eco-friendly solutions for turbid water problems in the community. This program proved not only academically relevant but also valuable in fostering environmental awareness.